Demographic Profile of Patients Undergoing Colonoscopy at a Tertiary Care Centre in Central Nepal - Belbase, Narayan Prasad; Karki, Mukesh; Dewan, Kush Raj; Mishra, Rohit (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Colonoscopy is one of the useful diagnostic tool to evaluate lower gastrointestinal tract. The aim of this study was to evaluate patient characteristics, common symptoms, colonoscopic findings and histopathology findings by reviewing colonoscopy procedures. Methods: This was a retrospective study conducted at College of Medical Sciences and teaching hospital, Bharatpur, Nepal over a period of three years (1st January 2017 – 31st December 2019). Census sampling method was used to retrieve the data. Patients characteristics, indications, duration of symptoms and findings were retrieved from the endoscopy record register and histopathology finding of those patients whose biopsy were taken were retrieved from the pathology department record file. Results: Over a three years period 324 colonoscopy were reviewed.The mean age of the study population was 48.77+/-17.35 years. Male to female ratio was 1.38:1. The most common indication for colonoscopy was pain abdomen with mucus in stool in 25.3% patients followed by bleeding per rectum in 21.3% patients. Other than normal colonoscopy the most common findings were Haemorrhoids in 20.1% patients and inflammatory or ulcerative lesions in 17.6% patients. Colorectal malignancy was seen in 6.48% patients. Colonoscopic biopsy was done in 114 patients. The common biopsy findings were ulcerative colitis in 12.7%, adenomatous polyp in 6.8%, adenocarcinoma in 6.5% of the total study patients.Poorly differentiated carcinoma was found more in the younger age group and males were more commonly affected with colorectal cancers than females. Conclusions: The most common indication for colonoscopy was pain abdomen with mucus in stool in 25.3% patients. The common findings were Haemorrhoids in 20.1% patients and inflammatory or ulcerative lesions in 17.6% patients. Colorectal malignancy was seen in 6.48% patients. The common biopsy findings were ulcerative colitis in 12.7%, adenomatous polyp in 6.8%, adenocarcinoma in 6.5% of the total study patients. Males were more commonly affected with colorectal cancers than females. Keywords: Colonoscopy, lower gastrointestinal tract, colorectal cancer, ulcerative colitis, haemorrhoids.